DESIGN OF THE INTERACTIVE ILLUSTRATION BOOK “LET'S PLAY HIDE AND SEEK” FOR CHILDREN AGED 3+ - Martinus Eko Prasetyo (Institut Seni Indonesia Yogyakarta, 2022)
This interactive illustration book “Let’s Play Hide and Seek” is in the form of stories with animals characters in the book that can attract children's attention and also teaches them to recognize the animals in this illustration book. The research method that the author uses in this study is using qualitative methods with survey or questionnaire data collection methods, literature studies and interviews. The author will distribute questionnaires to research respondents, especially the child's parents or relatives who are older than the child and ask them to fill out the questionnaire. The design of the interactive illustration book “Let’s Play Hide and Seek” for children aged 3 years above was made with the aim of the author being able to make books that can attract children's interest in reading from an early age and entertain children aged 3 years above who read this book while strengthening interactions between children. parent and child so that they become closer when they read this book together.